Forest edge landscape context affects mosquito community composition and risk of pathogen emergence - Adam Hendy; Nelson Ferreira Fé; Igor Pedrosa; André Girão; Taly Nayandra Figueira dos Santos; Claudia Reis Mendonça; José Tenaçol Andes Júnior; Flamarion Prado Assunção; Edson Rodrigues Costa; Vincent Sluydts; Marcelo Gordo; Vera Margarete Scarpassa; et al. (iScience)
Summary: Forest edges, where humans, mosquitoes, and wildlife interact, may serve as a nexus for zoonotic arbovirus exchange. Although often treated as uniform interfaces, the landscape context of edge habitats can greatly impact ecological interactions. Here, we investigated how the landscape context of forest edges shapes mosquito community structure in an Amazon rainforest reserve near the city of Manaus, Brazil, using hand-nets to sample mosquitoes at three distinct forest edge types. Sampling sites were situated at edges bordering urban land cover, rural land cover, and natural treefall gaps, while sites in continuous forest served as controls. Community composition differed substantially among edge types, with rural edges supporting the highest species diversity. Rural edges also provided suitable habitat for forest specialists, including key sylvatic vectors, of which Haemagogus janthinomys was the most abundant species sampled overall. Our findings emphasize the importance of landscape context in assessing pathogen emergence risk at forest edges.